Analysing the Impact of ESG Implementations on the Financial Performance of Indian Companies and Related Biases - Dutta, Chandan (Digital Repository of Theses, 2025)
This research studied the role of ESG implementations on the financial performance of companies within India. It also explored the relationships between ESG scores and financial performance, between industry sectors and ESG scores, and company biases towards specific ESG parameters. The study used content analysis of online reports and data, and conceptual modeling to identify the relationship between ESG and financial performance. The primary objective of the research was to study the impact of ESG implementations on the financials of companies within India and the aptitude of Indian companies towards various ESG parameters. This study provided insights on what kind of ESG implementations have a greater impact on firm financials. The study also builds a greater understanding of the intricate relationship between environmental, social and governance initiatives, and financial performance. Finally, the study adds to the existing literature with an Indian focus which now is very sparse. Keywords: ESG (Environmental, Social, Governance), financial performance, company biases, content analysis, conceptual modeling, ESG parameters.